2017
DOI: 10.1007/s10534-017-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal chelators on the aggregation of beta-amyloid peptides in the presence of copper and iron

Abstract: Amyloid β (Aβ) fibrils and amorphous aggregates are found in the brain of patients with Alzheimer's disease (AD), and are implicated in the etiology of AD. The metal imbalance is also among leading causes of AD, owing to the fact that Aβ aggregation takes place in the synaptic cleft where Aβ, Cu(II) and Fe(III) are found in abnormally high concentrations. Aβ40 and Aβ42 are the main components of plaques found in afflicted brains. Coordination of Cu(II) and Fe(III) ions to Aβ peptides have been linked to Aβ agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Several reported fluorescence studies based on the ThT dye have been performed in different experimental conditions (solvent used for Aβ, pH, and incubation time), which turn difficult comparison of results. Under our experimental method it was observed a tendency for decreasing the fluorescence intensity for Aβ in the presence of copper, in comparison with its absence, which may be due to some precipitation of amorphous deposits of the peptide rather than formation of β sheets [38,39]. In former studies, with TAC-BIM derivatives (1, 2) [22,23,33], a fluorescence-independent method like transmission electron microscopy (TEM) was used, due to possible quenching interferences in the emission of the paramagnetic copper ion, and it was observed that scarcer aggregates appear in the presence of Cu(II) when comparing Aβ with Aβ + Cu(II).…”
Section: Inhibition Of Aβ 1-42 Aggregationmentioning
confidence: 65%
See 1 more Smart Citation
“…Several reported fluorescence studies based on the ThT dye have been performed in different experimental conditions (solvent used for Aβ, pH, and incubation time), which turn difficult comparison of results. Under our experimental method it was observed a tendency for decreasing the fluorescence intensity for Aβ in the presence of copper, in comparison with its absence, which may be due to some precipitation of amorphous deposits of the peptide rather than formation of β sheets [38,39]. In former studies, with TAC-BIM derivatives (1, 2) [22,23,33], a fluorescence-independent method like transmission electron microscopy (TEM) was used, due to possible quenching interferences in the emission of the paramagnetic copper ion, and it was observed that scarcer aggregates appear in the presence of Cu(II) when comparing Aβ with Aβ + Cu(II).…”
Section: Inhibition Of Aβ 1-42 Aggregationmentioning
confidence: 65%
“…In fact, it is well known that Aβ binds Cu(II) and, although this interaction has been associated to the induction of Aβ aggregation [15,16], it has also been admitted that it can lead to the precipitation of amorphous deposits of the peptide and not to ThT-positive β sheet rich amyloid fibril formation with different studies being performed on the analysis of the effect of Cu(II) on the propensity for Aβ fibril formation as well as on the effect of metal chelators on this process [38,39]. Several reported fluorescence studies based on the ThT dye have been performed in different On the other hand, Figure 5B shows the effect of substituent groups, as R 1 in the BIM moiety or R 2 in the benzyl of the PZ unity.…”
Section: Inhibition Of Aβ1-42 Aggregationmentioning
confidence: 99%
“… 116 For example, metal coordination is known to alter the aggregation kinetics and morphology of Aβ aggregates. 117 Metal ions in unpolarized atomistic simulations are treated as simple van der Waals spheres, nonbonded models with atoms, or with bonded models by employing artificial bonds. 118 Nevertheless, the polarization effects are crucial, as the polarization energy can range from very small values to values around 10–20% for the total interaction energy.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also found that iron can promote aggregation of Aβ peptides and increase their cytotoxicity ( Tahmasebinia and Emadi, 2017 ; Galante et al, 2018 ). However, there are different opinions on the role of iron and Aβ.…”
Section: Brain Iron Dyshomeostasis and The Pathophysiology Of Alzheimmentioning
confidence: 99%
“…Moreover, CQ treatment can effectively prevent an iron-synuclein interaction in hA53T transgenic mice ( Billings et al, 2016 ), as well as reverse the Fe 3+ -induced fibrin formation in vitro ( Pretorius et al, 2013 ). Importantly, the formation of Aβ40 and Aβ42 aggregates in the presence of Fe 3+ and Cu 2+ were investigated, the study demonstrated that Fe 3+ , but not Cu 2+ , promotes the aggregation of Aβ40 and Aβ42, and CQ significantly reduces the Fe 3+ -induced Aβ42 aggregation ( Tahmasebinia and Emadi, 2017 ). These researches provide the evidence that the anti-AD ability of CQ may, at least in part, via targeting iron and, surely, the underlying mechanism need to be further elucidated, Although it is now thought that CQ is toxic to the body, it at least opens up a promising direction for us.…”
Section: Iron-targeting Treatment Strategiesmentioning
confidence: 99%